2020
DOI: 10.1214/19-sts728
|View full text |Cite
|
Sign up to set email alerts
|

Outcome-Wide Longitudinal Designs for Causal Inference: A New Template for Empirical Studies

Abstract: In this paper, we propose a new template for empirical studies intended to assess causal effects: the outcome-wide longitudinal design. The approach is an extension of what is often done to assess the causal effects of a treatment or exposure using confounding control, but now, over numerous outcomes. We discuss the temporal and confounding control principles for such outcome-wide studies, metrics to evaluate robustness or sensitivity to potential unmeasured confounding for each outcome and approaches to handl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
309
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 215 publications
(311 citation statements)
references
References 134 publications
(213 reference statements)
2
309
0
Order By: Relevance
“…An outcome-wide approach was applied, in which multiple outcomes were considered for a single exposure (VanderWeele 2017a ). This approach has been theoretically argued (VanderWeele 2017a ; VanderWeele et al 2020b , a ) and empirically confirmed as effective in presenting temporal associations across the whole spectrum of outcomes (Białowolski et al 2019 ; Chen et al 2019 ; Chen and Vanderweele 2018 ; Kim et al 2020 ; Pawlikowski et al 2019 ; Steptoe and Fancourt 2020 ; Węziak-Białowolska et al 2018 ). It has the advantage of avoiding cherry-picking of significant results only, limits the risk of p-hacking (Head et al 2015 ; Lakens 2015 ) and seems to facilitate reporting of the so-called ‘negative’ or ‘non-significant’ findings, which has been already proven problematic in scientific publishing due to resistance of journal editors to publish negative results (Fanelli 2010 , 2012 ; Ioannidis 2005 ; Matosin et al 2014 ).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…An outcome-wide approach was applied, in which multiple outcomes were considered for a single exposure (VanderWeele 2017a ). This approach has been theoretically argued (VanderWeele 2017a ; VanderWeele et al 2020b , a ) and empirically confirmed as effective in presenting temporal associations across the whole spectrum of outcomes (Białowolski et al 2019 ; Chen et al 2019 ; Chen and Vanderweele 2018 ; Kim et al 2020 ; Pawlikowski et al 2019 ; Steptoe and Fancourt 2020 ; Węziak-Białowolska et al 2018 ). It has the advantage of avoiding cherry-picking of significant results only, limits the risk of p-hacking (Head et al 2015 ; Lakens 2015 ) and seems to facilitate reporting of the so-called ‘negative’ or ‘non-significant’ findings, which has been already proven problematic in scientific publishing due to resistance of journal editors to publish negative results (Fanelli 2010 , 2012 ; Ioannidis 2005 ; Matosin et al 2014 ).…”
Section: Methodsmentioning
confidence: 90%
“…Because of the longitudinal panel data employed, in contrast to many cross-sectional analyses, our approach attempted to offer more plausible evidence for causality by ensuring a logical temporal sequence of cause and effect from the data (VanderWeele et al 2020a , b ; VanderWeele et al 2016a , b ). Specifically, since two exposure variables were measured temporarily prior to outcomes, the intended causal links were more plausible.…”
Section: Methodsmentioning
confidence: 99%
“…This could be done in an online supplementary table, with some comment given in the main text. In outcome-wide settings in which numerous outcomes, 10 , 11 and thus numerous E-values, are assessed, a single table perhaps reporting the three largest covariate–outcome associations (properly inverted for protective associations) for each outcome could once again be helpful. In principle, a similar approach might also be used for the exposure, by providing the largest exposure–covariate relative risk associations across covariates.…”
Section: Assessing Confounding Association Magnitudesmentioning
confidence: 99%
“…There has been growing interest in examining multiple categories of outcomes within the same study, which can potentially reduce publication bias and provide a broader picture of the complex religion–health dynamics. 24 , 25 Finally, religious involvement is often characterized by a cyclic structure across a lifetime, often with a return to religious community in later life. Prior work has, however, seldom compared the religion–health associations across life stages.…”
Section: Introductionmentioning
confidence: 99%